ANOMALI POLITIK MEDIA PEMBERITAAN POLRI VERSUS KEJAGUNG: Studi Kasus Pemberitaan Peristiwa Intervensi Densus 88 Polri Pada Jampidsus Dalam Penanganan Kasus Korupsi di Kejaksaan Agung - Algooth Putranto; Slamet Budiharjo (Jurnal Komunikasi & Media Digital, 2024)
In today's digital era, where everything moves and changes rapidly, the media in its journalistic work, is under demands that it must be able to provide information about events or occurrences as quickly as possible. The digitalization of conventional media opens up the possibility of media convergence which will impact not only the media industry but also changes in media consumption patterns, public perception, information dissemination, and media literacy. The incident of stalking of the Deputy Attorney General for Special Crimes (Jampidsus) carried out by members of Counterterrorism Special Detachment 88 Indonesian National Police was revealed by the media who were unable to fully explain the background and how the incident occurred. Tribunnews.com has footage, but the media did not publish the news related to this incident because of difficulties for the media to carry out verification. This research highlights reporting by Kompas.com and Tribunnews.com, two online media that are members of the Kompas Gramedia Media Group, using descriptive qualitative research methods with an approach to media political theory and media management related to reporting on the feud between the Attorney General's Office and the National Police.